Competency-based curriculum in Shariah accounting study program in Indonesia - Violita, Evony Silvino; Siswantoro, Dodik; Abdullah, Wasilah; Nurhayati, Sri (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study aimed to evaluate the curricula of the Study Program in Shariah Accounting in Indonesia. This research also proposes a particular curriculum for study programs on Shariah accounting in Indonesia.Methodology – The curricula are evaluated using a competency-based approach towards some study programs. For this purpose, this study conducts a comparative research method by comparing the expectations of the industry with the curricula of six (6) undergraduate study programs in Shariah account-ing. This step is followed by conducting several interviews with the head of the study programs as well as the practitioners to support the qualitative analysis.Findings – The research finds that existing curricula need some improvement to meet the expectations of the industry. Some new subjects offered for the proposed competency-based curriculum are related to risk management, management control systems, the digital economy, leadership, Islamic entrepreneurship, ethics and governance, data analytics, and personal financial planning.Implications – Study programs in developing curricula should consider the comprehensiveness of the curricula and balance the aspects of knowledge, skills, ethics, and governance. Discussion forums among study programs in Indonesia can produce a curriculum that can be used as a standard or benchmark for their own study programs.Originality – Evaluating the existing curricula of the Shariah accounting program in Indonesia has not yet been conducted or discussed in the literature more intensely. This study analyzed curricula based on competencies. Hence, it can align graduates’ competencies with the needs of the industry.